Problems of Tourism Leakage in Badung Regency due to Foreign Tourist Invasion - Margayawati, Ni Luh Putu; Dewi, Nyoman Diah Utari; Widnyani, Ida Ayu Putu Sri (Journal of Sustainable Tourism and Entrepreneurship, 2025)
Purpose: Bali Province, a popular tourist destination, is facing challenges due to the "Foreign Tourist Invasion." This term refers to foreign tourists dominating the local economy by establishing illegal businesses, such as restaurants, tour services, and money changers. These operations often evade taxes and negatively affect local enterprises. Research Methodology: This study employed a qualitative descriptive approach using a case study method. Data were collected through in-depth interviews, direct observations, and document analysis in tourism hotspots, such as Kuta, Seminyak, and Nusa Dua. Results: The study reveals that tourism leakage is caused by the weak enforcement of regulations, the dominance of foreign-owned businesses, and minimal local community involvement. Consequently, most tourism revenue benefits foreign investors rather than local residents. Conclusion: To mitigate leakage, this study recommends strengthening community-based tourism (CBT), supporting local SMEs, enforcing tourism-related regulations, and diversifying tourism markets to include more domestic travelers. Limitations: The study's findings are geographically limited to major tourist zones in Badung Regency and rely on qualitative data, which may not fully capture broader statistical patterns across Bali, Indonesia. Contributions: This study provides strategic insights for policymakers and tourism stakeholders by highlighting the need for structural reforms in tourism governance. It also raises awareness of the long-term socioeconomic implications of unmanaged tourism and advocates for sustainable, inclusive tourism development rooted in local participation.